2001
DOI: 10.1007/pl00006956
|View full text |Cite
|
Sign up to set email alerts
|

Major colour patterns of reef-building corals are due to a family of GFP-like proteins

Abstract: Reef-building corals are renowned for their brilliant colours yet the biochemical basis for the pigmentation of corals is unknown. Here, we show that these colours are due to a family of GFP-like proteins that¯uoresce under ultraviolet (UV) or visible light. Pigments from ten coral species were almost identical to pocilloporin (Dove et al. 1995) being dimers or trimers with approximately 28-kDa subunits. Degenerative primers made to common N-terminal sequences yielded a complete sequence from reef-building cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
231
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 236 publications
(236 citation statements)
references
References 15 publications
4
231
1
Order By: Relevance
“…Our results demonstrate clearly that FP fluorescence of P. lobata can be used for non-invasive optical monitoring of the stress response of the host tissue. Regarding the putative photoprotective function of GFP-like proteins (Dove et al, 2001;Salih et al, 2000;Wiedenmann et al, 1999), the consistent downregulation under heat stress does not support any superior FP-mediated protection of the experimental Abu Dhabi specimens.…”
Section: Temperature Challenge Experimentsmentioning
confidence: 94%
See 2 more Smart Citations
“…Our results demonstrate clearly that FP fluorescence of P. lobata can be used for non-invasive optical monitoring of the stress response of the host tissue. Regarding the putative photoprotective function of GFP-like proteins (Dove et al, 2001;Salih et al, 2000;Wiedenmann et al, 1999), the consistent downregulation under heat stress does not support any superior FP-mediated protection of the experimental Abu Dhabi specimens.…”
Section: Temperature Challenge Experimentsmentioning
confidence: 94%
“…These host pigments belong to the family of GFP-like proteins (Alieva et al, 2008;Dove et al, 2001;Oswald et al, 2007;Wiedenmann et al, 2004Wiedenmann et al, , 2009) of which several (but not all) are regulated at transcriptional level in reef corals in response to changes in environmental conditions; in particular by blue light (Bay et al, 2009;D'Angelo et al, 2008;Desalvo et al, 2008;Leutenegger et al, 2007;Smith-Keune and Dove, 2007). Only recently, the expression of red FPs in the growth zones, wounded or epibiont-infested colony parts of P. lobata was correlated with areas characterised by accelerated cell proliferation .…”
Section: Fluorescent Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pigments responsible for the pink-blue pigmentation of reef coral response belong to the family of GFP-like proteins (Dove et al 2001;Wiedenmann et al 2004bWiedenmann et al , 2009Oswald et al 2007;Alieva et al 2008;D'Angelo et al 2008). Based on their photophysical properties, they can be divided into two major groups: the fluorescent proteins (FPs), emitting photons in the spectral range from cyan to red upon stimulation with light of suitable wavelengths, and the non-fluorescent chromoproteins (CPs), which display bright purple to blue colours (Prescott et al 2003;Alieva et al 2008;Nienhaus and Wiedenmann 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Finer detail showed that the symbiotic zooxanthellae (Zs) were encased in host 318 endodermal tissue (En), a feature common with whole corals ). This comparable cell 319 type composition provides a better means for investigating how nutrients and carbon are transferred 320 between the host and symbiont at a microscale ( In some instances they are proposed to do both, depending on the position of the fluorescent pigment 330 relative to the zooxanthellae (Dove et al 2001). In present study, it is possible that they fulfil a dual 331 role, as the explants were grown at relatively low light, and showed relative sensitivity to very high 332 light (Fig.…”
mentioning
confidence: 99%